The Comparison of the Effect of Three Commercial Soybean Meal Samples (Iranian, Argentinean and Brazilian) on Performance and Internal Organs Weight of Japanese Quails (Coturnix coturnix japonica) and Conducting Urease Test for These Soybeans - Ebrahimnezhad, Y.; Tajaddini, M.H.; Ahmadzadeh, A.R.; Shahriar, H. Aghdam (Pakistan Journal of Nutrition, 2012)
This experiment was carried out to compare and evaluate three commercial soybean meal samples (Iranian, Argentinean and Brazilian) and their effects on Body Weight Gain (BWG), Feed Intake (FI), Feed Conversion Ratio (FCR) and visceral organs weight (carcass, liver, pancreas, spleen and heart as percentage of live body weight) of Japanese quails (Coturnix coturnix japonica). A completely randomized design was used with three treatments and four replicates and in each, 20 parts were designed. Test treatments include: 1) basal diet + Iranian soybean meal, 2) basal diet + Argentinean soybean meal, 3) basal diet + Brazilian soybean meal. Raising duration was 42 days. Urease test was done on three soybean meal samples before test while results were negative. Also, results of using three commercial soybean samples showed no effect on body weight gain, feed intake, feed conversion ratio, carcass, heart, liver and spleen weight in Japanese ones but results revealed that soybean samples have had significant effect on pancreas weight.